2003
DOI: 10.2337/diacare.26.4.1064
|View full text |Cite
|
Sign up to set email alerts
|

Utility of HbA1c Levels for Diabetes Case Finding in Hospitalized Patients With Hyperglycemia

Abstract: OBJECTIVE -We evaluated the role of a single measurement of HbA 1c in a diabetes case finding in hospitalized patients with random hyperglycemia at admission. RESEARCH DESIGN AND METHODS -From 20March to 31 July 2000, 508 patients admitted through the emergency department of one hospital were tested for random hyperglycemia (plasma glucose [PG] Ͼ125 mg/dl). Consenting patients with hyperglycemia (without preexisting diabetes or on corticosteroids) underwent testing for HbA 1c levels, two fasting PG levels, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
119
1
8

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(129 citation statements)
references
References 25 publications
1
119
1
8
Order By: Relevance
“…25 We found wide variation among hospitals (range, 12.1%-76.5%) in use of recommended regimens of insulin therapy, defined as short-acting and long-acting subcutaneous insulin or IV insulin infusion or insulin pump therapy on second measurement day. Endocrine/diabetes consultation was infrequent, only 9% of all patients were evaluated by an endocrinologist or diabetologist at any time during the hospitalization.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…25 We found wide variation among hospitals (range, 12.1%-76.5%) in use of recommended regimens of insulin therapy, defined as short-acting and long-acting subcutaneous insulin or IV insulin infusion or insulin pump therapy on second measurement day. Endocrine/diabetes consultation was infrequent, only 9% of all patients were evaluated by an endocrinologist or diabetologist at any time during the hospitalization.…”
Section: Resultsmentioning
confidence: 92%
“…Also, measurement of A1C can be used for diabetes case-finding in hospitalized patients with hyperglycemia. 25 Previously unrecognized diabetes is a common finding in patients admitted with cardiovascular disease. In a study of patients admitted with myocardial infarction, 25% were found to have previously undiagnosed diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…No ADA diagnostic thresholds for the HbA1c currently exist, but it can be a useful marker in making this distinction. 56 Among patients with new hyperglycemia, an HbA1c of 6% or greater was 100% specific for predicting a future diagnosis of diabetes in the small prospective cohort study by Greci et al, 57 but many endocrinologists use a cutoff of 7%. For all hyperglycemic patients, lifestyle interventions that promote weight loss and increased activity levels should be encouraged.…”
Section: Transitioning From the Hospitalmentioning
confidence: 99%
“…Targets ranging from 120-250 mg!dl [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] have been advocated.…”
Section: Treatment Targetsmentioning
confidence: 99%
“…Approximately 12% of all hyperglycemic patients being admitted to tertiary care setting have no previous diagnosis of diabetes [6]. Sixty percent of patients with admission hyperglycemia developed confirmed diabetes at one year in a small study [7].…”
Section: Introductionmentioning
confidence: 99%